31st AIAA Applied Aerodynamics Conference 2013
DOI: 10.2514/6.2013-2797
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Synthetic-Jet-Based Flow Control for Performance Enhancement of a Vertical Stabilizer

Abstract: The performance enhancement of a vertical tail using synthetic jet actuators may allow for a decrease in tail size, which would result in a reduction of the drag, weight, and fuel consumption of the airplane. The potential for enhancement was investigated during wind tunnel experiments with a 1/19 th scale wind tunnel model of a Boeing 767 vertical tail at a Reynolds number of 350,000. The model was instrumented with twelve finite span synthetic jet actuators placed slightly upstream of the rudder hinge-line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…AFC on VTP with synthetic jets has also been studied both experimentally [22]- [24] and numerically [25]- [26]. A side force increment of 18% was obtained for C μ = 0.7% and a non-dimensionalized rudder deflection angle δ* equal to 0.5 [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFC on VTP with synthetic jets has also been studied both experimentally [22]- [24] and numerically [25]- [26]. A side force increment of 18% was obtained for C μ = 0.7% and a non-dimensionalized rudder deflection angle δ* equal to 0.5 [22].…”
Section: Introductionmentioning
confidence: 99%
“…AFC on VTP with synthetic jets has also been studied both experimentally [22]- [24] and numerically [25]- [26]. A side force increment of 18% was obtained for C μ = 0.7% and a non-dimensionalized rudder deflection angle δ* equal to 0.5 [22]. Different types of synthetic jet actuation have been compared and it was concluded that a purely sinusoidal waveform was more effective up to a deflection angle δ* = 0.8 but for higher angles, a pulse-modulated waveform at reduced frequency close to one was more effective while reducing the power by 80%.…”
Section: Introductionmentioning
confidence: 99%